Studi Analisis Deskriptif Kesalahan Fonologis dalam Percakapan Bahasa Arab terhadap Santri di Pesantren Mafaza Indonesia - Lina Marlina; Acep Hermawan; Firmansah Setia Budi (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2023)
This study aims to analyze studentsâ€™ pronunciation errors in their daily conversations using Arabic which implicated towards changing the meaning at the Mafaza Indonesia Islamic Boarding School, so that solutions can then be found in order to improve and enhance their speaking skill. This study was a qualitative descriptive research with content analysis design. The data collection process used two techniques, namely observation and interview. The results of this study showed that phonological errors which impacted on semantic changes occur in Arabic letters but these letters were not found in students' mother language. They were (Ø¹ØŒ Ø«ØŒØ´ØŒØµØŒÙ‚ ØŒØ²ØŒØ°ØŒØ¶ØŒØ). The solutions that can be one of an alternative to minimize the phonological errors were the phonetic method and the mim-mem method. This study contribute to increasing teacher competences by evaluating the Arabic learning curriculum both in terms of the duration of learning, the material or the methods used.